L'homme armé Expériences de la guerre et du combat en Castille au xve siècle - Baloup, Daniel (Bibliothèque de la Casa de Velázquez, 2022)
Based on the noble chronicles of the Trastamare period, this study seeks to establish how war was lived and narrated in Castile in the fifteenth century. The first two chapters deal with the production conditions of these texts, and address the problems that arise in the narration of the lived experience. The next three chapters show that the culture of war was widely shared among the nobility, regardless of gender or status: women and clerics were not excluded. On the other hand, the discourse on war constructs a form of nobiliary exclusivity that is manifested in the narrative treatment reserved for commoners. The last chapter finally approaches combat from an anthropological perspective, focusing on the warrior's body and emotions.